Using children's developmental psychology to guide augmented-reality design and usability - Radu, I.; MacIntyre, B. (2012 IEEE International Symposium on Mixed and Augmented Reality, 2012)
Augmented reality (AR) designers have great potential to enrich children's lives through AR experiences in education and entertainment. A significant difficulty in designing for children is that tremendous physical and cognitive development occurs across the first 10 years of life, and the changes in children's capabilities and limitations impact how these users respond to AR designs. Currently, little is known about how developmental changes relate to AR designs, or what AR designs are effective for young children. In this work, we focus on children 6-9 years old, presenting several concepts from developmental psychology and discussing how these relate to AR designs. Specifically, we investigate children's skills in the categories of motor abilities, spatial cognition, attention, logic and memory, and we discuss the relationship of these skills to current and hypothetical AR designs. Through this work, we intend to strengthen the field's understanding of AR usability and design, resulting in the generation of effective AR experiences for young users.